Aerobic Activity in the Healthy Elderly Is Associated with Larger Plasticity in Memory Related Brain Structures and Lower Systemic Inflammation - Thielen, Jan-Willem; Kärgel, Christian; Müller, Bernhard W.; Rasche, Ina; Genius, Just; Bus, Boudewijn; Maderwald, Stefan; Norris, David G.; Wiltfang, Jens; Tendolkar, Indira (Frontiers in Aging Neuroscience, 2016)
Abstract: Cognitive abilities decline over the time course of our life, a process, which may be mediated by brain atrophy and enhanced inflammatory processes. Lifestyle factors such as regular physical activities have been shown to counteract those noxious processes and are assumed to delay or possibly even prevent pathological states such as dementing disorders. Whereas the impact of lifestyle and immunological factors and their interactions on cognitive aging have been frequently studied, their effects on neural parameters as brain activation and functional connectivity are less well studied. Therefore we investigated thirty-two healthy elderly individuals (60.4 ± 5.0 SD; range 52-71 years) with low or high level of self reported aerobic physical activity at the time of testing. A higher compared to a lower level in aerobic physical activity was associated with an increased encoding related functional connectivity in an episodic memory network comprising mPFC, thalamus, hippocampus precuneus and insula. Moreover, encoding related functional connectivity of this network was associated with decreased systemic inflammation, as measured by systemic levels of interleukin 6.